Mechanical design - Abdullah, Mohd Azman; Mat, Shafizal; Shamsudin, Shamsul Anuar; Yob, Mohd Shukri (Penerbit UTeM Press, 2023)
This module is a reference manual for engineering students at Universiti Teknikal Malaysia Melaka. It fits the requirements of the BMCG 3333 Mechanical Design course. This module has six chapters and covers the topics of mechanical design and power transmission.